Albuminuria in patients with young onset type 2 diabetes - Yassamine Bentata; Redouane Abouqal (Society of Diabetic Nephropathy Prevention, 2017)
Introduction: Findings from several studies have indicated that patients with young onset diabetes (YOD) are more likely than those with late-onset diabetes (LOD) to have poor metabolic control and more diabetes-associated complications. Objectives: This study was to assess assess the profile at admission and the evolution in a cohort of young patients presenting type 2 diabetes (T2D) and to study the influence of glycemic control on progression of albuminuria. Patients and Methods: This is a prospective study. Inclusion criteria targeted patients who had T2D diagnosed before the age of 40 years and had been regularly followed in nephrology consultation for at least 36 months. Results: A total of 121 patients met the inclusion criteria. Mean age at diabetes diagnosis was 39 ± 3 years and 64.5% were female. Mean body mass index (BMI) was 28.02 ± 4.47 kg/m2. 22.3%, 57.9% and 19.8% had respectively, negative, micro- and macro-albuminuria. 22.3% were hypertensive, 36.4% had controlled diabetes and 14.9% had an estimated glomerular filtration rate (GFR) of <60 mL/min/m2. At the end of follow-up, 27.3% were hypertensive, 24% had controlled diabetes, 27.3% had negative albuminuria, 17.4% showed rapid renal progression and cardiovascular events occurred in 12.4% of cases. Conclusion: Control of blood pressure, glycemia and albuminuria remain difficult to achieve in adults with YOD type 2, thus exacerbating the renal and cardiovascular disease (CVD) risk